Fisheries assessment, gametogenesis and culture practice of local bivalve: a review - Hamli, Hadi; Idris, Mohd Hanafi; Mustafa Kamal, Abu Hena; Rajaee, Amy Halimah (Universiti Putra Malaysia Press, 2019)
Hard clams are found to overwhelm the benthic territory from the remote oceans in the marsh region, especially the tropical region. It is a filtered feeder that feeds upon microorganisms, debris and dissolved primal matter as the metabolic vitality hotspot for development. The abundance of food source caused mariculture of hard clam a possible practice in the open sea. Although harvested hard clams through mariculture progressively increase each year, they are still found to be less than oyster and cockle production. Knowledge of gametogenesis is essential for shellfish culture with a specific end goal to resolve the appropriate conditions for breeding. The gametogenesis is ordered into six phases, i.e. resting, early advancement, late advancement, ripe, spawning and spent. Fertilisation between sperm and egg occurs after hard clam spawning by chemical and physical incitement in the environment. Inseminated eggs experience several phases, i.e.; trochopores, D shape hatchlings, umbonal hatchlings and juvenile phase before ending up as mature shellfish. This review is chiefly intended to cover the biology and culture capability of hard clams, especially in Malaysia.